Effect of Particle Size on Pore Structure and Fractal Characteristics of Deep Siliceous Shales in Southern Sichuan, China, Measured Using Small-Angle Neutron Scattering and Low-Pressure Nitrogen Adsorption - Hongming Zhan; Xizhe Li; Zhiming Hu; Liqing Chen; Weijun Shen; Wei Guo; Weikang He; Yuhang Zhou (Fractal and Fractional)
Granular samples are often used to characterize the pore structure of shale. To systematically analyze the influence of particle size on pore characteristics, case studies were performed on two groups of organic-rich deep shale samples. Multiple methods, including small-angle neutron scattering (SANS), low-pressure nitrogen gas adsorption (LP-N2GA), low-pressure carbon dioxide gas adsorption (LP-CO2GA), and XRD analysis, were adopted to investigate how the crushing process would affect pore structure parameters and the fractal features of deep shale samples. The research indicates that with the decrease in particle size, the measurements from nitrogen adsorption and SANS experiments significantly increase, with relative effects reaching 95.09% and 51.27%, respectively. However, the impact on carbon dioxide adsorption measurements is minor, with a maximum of only 8.97%. This suggests that the comminution process primarily alters the macropore structure, with limited influence on the micropores. Since micropores contribute the majority of the specific surface area in deep shale, the effect of particle size variation on the specific surface area is negligible, averaging only 16.52%. Shales exhibit dual-fractal characteristics. The distribution range of the mass fractal dimension of the experimental samples is 2.658–2.961, which increases as the particle size decreases. The distribution range of the surface fractal dimension is 2.777–2.834, which decreases with the decrease in particle size.